Historisitas Tahfiz al-Qur’an: Upaya Melacak Tradisi Tahfiz di Nusantara - Noer, Syaifudin (JOIES (Journal of Islamic Education Studies), 2017)
The tradition of tahfiz (reciting the Qur'an) dates from the time of the Prophet. that the Messenger of Allah had set with his companions. In Indonesia itself, the journey of how the tahfiz tradition goes through three main periods, namely pre-independence, post-independence until the Reformation era (MTQ 1981). During the pre-independence period, 5 sanads were found to have played a role in the spread of the Qur'an tahfiz and were the source of the huffazas at the tahfiz institution / boarding school, among them K.H. Muhammad Said bin Ismail Sampang, Madura, K.H. Munawaar of Sidayu, Greece, Muhammad Mahfudz al-Tarmasi. Termas Pacitan, K.H. Muhammad Munawwir Krapyak, Yogyakarta and K.H. M. Dahlan Khalil of Rejoso, J Wave. Post-independence came the rise of a new tahfiz institution led by K.H. Muntaha (1912-2004 AD) Percentries of Al 'Asy'ariyah Wonosobo-Central Java and K.H. Joseph Junaidi (1921-1987) Bogor. Over time, the post-Musafqah Hifz al-Qur'an (MHQ) tahfiz institution was developed on the islands of Java and Sulawesi, from 1981 to almost every region in the archipelago.